Pengukuran Kinerja Badan Usaha Koperasi dengan Balanced Scorecard - Achmad Achmad (Program Pascasarjana Universitas Ibrahimy, 2017)
Performance measurement is an important factor for the company. It can be used to assess the success and detect of debility in the company. It was focussed to financial affairs, which describe to the company condition in short-term, The success in the financial perspective cannot be separated from the other non-financial perspective. Balanced scorecard was counteracted the model of performance measurement are not based on financial affairs, but increased by customer’s perspective, internal business process perspective, and learning and growth perspective are the real of instigator to the successful financial performance. Balanced scorecard gived the balanced of standart among finacial aspect and non-financial, among short-term and long-term and was involved internal factor or eksternal of the company. Cooperation as implement national economic development, demanded to be able to develop themselves in an increasingly competitive business competition. Side by side with other sectors for progress Indonesian economy. Because of it, the cooperation need apllied all and good methode of performance measurement for estimating the company’s condition, concurrently for facility the development of business strategy. With Balanced scorecard, as continuousness cooperation can be determine program effectiveness and report performance improvement plan.